URGENSI PENDIDIKAN MULTIKULTURALISME DALAM PEMBELAJARAN SEJARAH JENJANG SMA - Arassuly, Maulana Yusuf; Djono, Djono (Universitas Negeri Surabaya, 2025)
Multiculturalism education in history learning in high school is essential to form a generation that is tolerant and respectful of diversity. This article discusses the urgency of integrating the values of multiculturalism in the learning history, which allows students to understand history from a variety of cultural perspectives. With this approach, students are expected to develop critical thinking skills, empathy, and inclusive attitudes, so that they can contribute to a more harmonious society. The methodologyaa used in this study is a literature review, which is the collection of data and informationfrom various sources, including scientific articles and reference books. A descriptive analysis approach is applied to describe and describe the data that has been collected, without making definitive conclusions. This research also explores the application of technology in history learning to increase students’ interest. The results of the study show that multi-year education.